2012
DOI: 10.1007/s00192-012-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

Does neuromuscular blockade affect the assessment of pelvic organ prolapse?

Abstract: Neuromuscular blockade leads to significantly greater increases in POP-Q examination measurements compared with the office measurements, and this increase is most pronounced apically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A recent study by Brazell et al examined the role of neuromuscular blockade and descent in the operating room and found that patients that had neuromuscular blockade had a larger difference in point C between the clinic and the operating room (3.4 cm with neuromuscular blockade and an endotracheal tube and 0.5 cm in those with a laryngeal mask airway) [8]. We did not find that use of a neuromuscular blockade agent affected the magnitude of the difference in point C in the office and the OR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Brazell et al examined the role of neuromuscular blockade and descent in the operating room and found that patients that had neuromuscular blockade had a larger difference in point C between the clinic and the operating room (3.4 cm with neuromuscular blockade and an endotracheal tube and 0.5 cm in those with a laryngeal mask airway) [8]. We did not find that use of a neuromuscular blockade agent affected the magnitude of the difference in point C in the office and the OR.…”
Section: Discussionmentioning
confidence: 99%
“…GH and Pb measured on straining were consistently stronger predictors of prolapse symptoms and objective prolapse (by clinician examination and by ultrasound) than at Gh and Pb measured at rest. Anesthesia/neuromuscular blockade: the effect of neuromuscular blockade on POP staging was examined by one study [ 19 ]. It was found that neuromuscular blockade during anesthesia led to a significant increase in POP-Q measurements, especially in the apical compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Anesthesia/neuromuscular blockade: the effect of neuromuscular blockade on POP staging was examined by one study [ 19 ]. It was found that neuromuscular blockade during anesthesia led to a significant increase in POP-Q measurements, especially in the apical compartment.…”
Section: Resultsmentioning
confidence: 99%